Towards Sustainable Development - Learning And Challenges Of Fishing Communities (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Implementation Of Actions To Achieve The Goals Of The Sustainable Development Goals Assumed By Each Nation Represents A Challenge That, To Date, Many Have Failed To Advance. Such Is The Case Of The Fishing Communities Of Colombia, That Despite Having Conditions For The Implementation Of Sustainable Fishing And Achieving The Comprehensive Quality Of Life That The Sdgs Propose, Its Achievement Is A Distant Goal. This Research Sought To Identify The Challenges Around Sustainable Development In Three Fishing Communities In The Colombian Caribbean, As Well As The Lessons Learned From Approaching Their Daily Lives. Two Semi-Structured Surveys And Direct Observation Were Used To Identify The Characteristics, Conditions, And Challenges Of The Participating Communities. The Results Show Common Aspects Within The Communities, But Also Significant Differences In Their Practices And Daily Life Despite Being In The Same Environment. The Challenges Of These Communities Are Concentrated In 12 Of The Sdgs From Which Their Situation Was Analyzed.